New Entropy Restrictions and the Quest for Better-Specified Asset-Pricing Models - Bakshi, Gurdip; Chabi-Yo, Fousseni (Journal of Financial and Quantitative Analysis, 2019)
This article proposes the entropy of m 2 ( m is the stochastic discount factor) as a metric to evaluate asset-pricing models. We develop a bound on the entropy of m 2 when m correctly prices a finite number of returns and consider models that pass the lower bound on m , yet fail the lower bound on m 2 . Interpreting our results, we elaborate on the distinction between the entropy of m 2 versus the entropy of m . We further show that the entropy of m 2 represents an upper bound on the expected excess (log) return of the security with the payoff of m .